Pidana Mati Terhadap Kejahatan Narkotika Ditinjau Dari Pasal 28I Ayat (1) UUD NRI 1945 - Roby Anugrah; Raja Desril; Hari Sutra Disemadi (Kertha Wicaksana, 2020)
The debate about capital punishment from classical to modern times is still a debate that has not found a dialogue point. From the Beccaria era which stated that capital punishment was not effective in tackling crime, many killings occurred and will continue to occur until today the pros and cons of capital punishment still maintain their respective arguments. In answering the problems regarding the pros and cons of capital punishment against narcotics crime, this study uses a qualitative analysis method with a type of normative legal research. The data used in normative legal research is, of course, secondary data obtained through library research. In Indonesia, the debate about capital punishment against narcotics criminals reappears to the public when the provisions of the threat of capital punishment in the Narcotics Law are submitted to a judicial review or judicial review to the Constitutional Court which is considered to conflict with the most basic human rights namely the right to life guaranteed by the 1945 Constitution. Whereas if the death penalty is investigated for narcotics crimes and other crimes in general as long as it is firmly regulated in statutory regulations it does not contradict the right to life that humans have from birth.